Penerapan Metode Design Thinking dalam Perancangan UI/UX Aplikasi Mobile SIPROPMAWA - Soni Ansori; Purwono Hendradi; Setiya Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sipropmawa is a web-based system designed to manage, monitor, and oversee the online submission of proposals. However, the use of the Sipropmawa website is still suboptimal and lacks attention to user interface (UI) and user experience (UX) design, especially when accessed through mobile devices, resulting in user discomfort when using the application. Therefore, the motivation behind this testing is to update the UI/UX of the Sipropmawa application from a website to a mobile-based application by implementing the design thinking method. The choice was made to adopt a design thinking approach because it emphasizes creativity in creating new solutions and places a strong emphasis on understanding user needs. This study involves the collection and analysis of data, which includes five stages of the design thinking method: empathize, define, ideate, prototype, and testing. The implementation of the design thinking method in the development of the user interface (UI/UX) yields results that can achieve the goals of the method, which is to enhance user satisfaction and utility. In this regard, the support relies on the results of usability testing, which achieved a final score of 86 and obtained a B classification on the rating scale. Thus, this indicates that users highly appreciate the usability of the Sipropmawa mobile application. The UI/UX design of the Sipropmawa application is expected to serve as a model for future development of the Sipropmawa application.